Treatment compliance and retention in care among out-patient clients in a tertiary health institution in plateau state North Central Nigeria - Afolaranmi, Tolulope O.; Hassan, Zuwaira I.; Mbak, Joy L.; Luka, Davou W.; Audu, Takzhir N.; Chirdan, Oluwabunmi O.; Zoakah, Ayuba I. (International Journal of Research in Medical Sciences, 2018)
Background: Compliance with prescribed treatment and retention in care are key components in the management of chronic diseases which is vital in averting the long term complications that could arise from such conditions. Failure to comply with treatment recommendations is often associated with poor retention in care. In view of this, this study was conducted to determine the level of treatment compliance and retention in care among patients with hypertension and diabetes in Jos University Teaching Hospital. Methods: This was a cross sectional study conducted among 290 eligible respondents between September and November 2017 using quantitative method of data collection. SPSS version 20 was used for data analysis with adjusted odds ratio and 95% confidence interval used as point and interval estimates while p-value of ≤0.05 was considered statistically significant. Results: The mean age of the respondents was 54.5±13.1 years with 43.8% of the respondents found to have satisfactorily complied with prescribed treatment while 117 (40.3%) were uninterruptedly retained in care within the last 6 months' clinic appointments prior to the study. Conclusions: This study has demonstrated the levels of compliance with treatment and retention in care bringing to bear the need to provide structured interventions targeted at attaining improvement in compliance with treatment and retention in care among individuals on long term care.